The effect of peer support education on dental caries prevention behavior in school age children at age 10-11 years old - Debby Syahru Romadlon; Taufan Bramantoro; Muhammad Luthfi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Dental caries is an infectious disease and it is preceded by a progressive demineralization in hard tissue surface of the crown. Dental caries is one of the most common diseases that experienced by school-age children. Health education on the prevention of dental caries and peer support education method can improve the behavior of caries prevention. Purpose: This study aimed to determine the effect of peer support education on dental caries prevention behavior in children of school age. Method: This study is a quasi-experimental design with pretest and posttest control group design. The sampling technique is simple random sampling. The study was conducted in SDN Bandulan 3 Sukun Malang with 35 respondents (experimental group) and in SDN Bandulan 2 Sukun Malang with 35 respondents (control group). The experimental group was treated using peer support education while the control group was given health education with the lecture method. The data of student’s dental caries prevention behavior (knowledge and attitudes) is obtained through a questionnaire. Data were analyzed using paired t-test and independent t-tests with significant p value <0.05. Result: The results showed the average score of knowledge in the experimental group at 20.48 and knowledge among respondents in the control group amounted to 18.02, and the average total score of the attitude of the respondents in the experimental group at 20.08 and in control group of 17.77. Results of independent t test analysis test that there is a significant difference in the average scores of knowledge and attitudes of respondents in the experimental group and the control group (p value 0.000, <0.05). Conclusion: Health education with peer support education method is effective in improving dental caries prevention behavior in children at school age.